Pengaruh Karakteristik Individu, Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja dan Komitmen Organisasi (Studi Pada Pemerintah Daerah Di Propinsi Sumatera Utara) - Lumbanraja, Prihatin (Universitas Brawijaya, Indonesia, 2009)
This study analyzes the influence of individual characteristic, leadership style and organizational culture toward work satisfaction and organizational commitment to prove the direct and indirect influence of individual characteristic, leadership style and organizational culture toward work satisfaction and organizational commitment, and the role of organizational culture and work satisfaction as intervening variable in various types of influence relationship. The implementation of local autonomy and globalization era to be a serious challenge for local government institution. Increasing of public demand toward service quality forced the local government to improve and increase the quality in internal as well as external aspect for achieving better professionalism. This study focus on internal improvement especially on work satisfaction and organizational commitment and individual characteristic, leadership style and organizational culture as antecedent variable which predict as cause of unprofessional management in local government organization. Sixteen from twenty five local government in North Sumatera Province are chosen as samples in this research, and staff with echelon rank II, III and IV as analysis unit. Multistage sampling technique is used base on cluster, stratified and purposive. By means of Slovin postulation, the respondent obtained are 326 people or 82,5%. The data analysis by applying structural equation modeling (SEM) to find out the various influence relationship intra variable research. While qualitative analysis is carried out to explore various information about phenomena that can not be explored by quantitative analysis. The research result indicated that, work satisfaction and organizational commitment were influenced by individual characteristic, leadership style and organizational culture, but individual characteristic and leadership style were not influenced toward organizational culture. Because of that condition, individual characteristic and leadership style were not influenced toward work satisfaction and organizational commitment through the organizational culture. In this case, the role of organizational culture that not maximum indicated that organizational culture in local government institution is not applied strongly yet by the organization members. Vice versa, the work satisfaction has quite important role, it is proven by the direct and indirect influence of work satisfaction not only as intervening variable of individual characteristic, leadership style and organizational culture toward organizational commitment, but also as antecedent toward organizational commitment.